Rock resistance of bored piles socketed into rock - Sharudin, Eda Suhaili (2016)
In view of the large movement required to mobilize the bearing resistance of bored piles and difficulty in base cleaning, the bearing resistance often ignored in current design practice that will result in excessive rock socket length. Many attempts have been made to correlate the bearing resistance with the unconfined compressive strength of intact rock and the RQD but it is uncertain how applicable they are to rock type in Malaysia. This paper attempts to review the applicability of the formulas from previous studies to rock in Malaysia. A program of field testing tests for 13 bored piles with diameter varying from 1000mm to 1500mm constructed in Malaysian granite was conducted to measure the axial response of bored piles and tested using static load test and high strain load dynamic test to verify its integrity and performance. The results were evaluated and compared to the predicted rock bearing resistance. Based on the result obtained, method by AASHTO gives the best prediction of rock bearing resistance for granite in Malaysia and the trend of the rock compressive strength and rock discontinuities were also scattered with relationship to rock bearing resistance.